Student’s Experiences Using ChatGPT for Academic Purposes - Acena, Joseph (Journal of Interdisciplinary Perspectives, 2024)
The presence of technology has made our lives more convenient, especially as it advances and develops over time. Compared to previous generations, it is evident that technology has greatly aided humans in reducing the number of tasks. However, the use of technology comes with great responsibility. Technology's convenience can sometimes be misused, leading to overuse. This can result in humans relying on artificial intelligence instead of using their natural intelligence. The main objective of this qualitative study is to explore the important insights of senior high school students using ChatGPT in their academics and the meanings ascribed to their experiences. Data was generated from in-depth semi-structured interviews utilizing the transcendental phenomenological design and analyzed through thematic analysis. The analysis revealed that as students become more familiar with ChatGPT, their perspectives change, recognizing its importance and limitations. They acknowledge ChatGPT's potential as the future of education, but caution against excessive reliance and potential loss of essential learning experiences. They now accept it as a helpful guide, not a means of cheating. The findings suggest that students should use ChatGPT, as a supplement to their thinking and learning process, balancing technology with personal experiences. Moreover, educators and school administrators should promote responsible use of AI tools like ChatGPT. Students to critically evaluate information and cross-reference it with reliable sources.